1999
DOI: 10.1007/s002109900129
|View full text |Cite
|
Sign up to set email alerts
|

Imidazoline derivatives and agmatine induce histamine release from the rat stomach

Abstract: Strips from rat glandular stomach were used to investigate whether the imidazoline derivatives clonidine, tolazoline and BDF 6143 (4-chloro-2(2-imidazolin-2-ylamino)-isoindoline) and the guanidine derivative agmatine are able to release histamine from histamine-storing cells. Histamine was detected and quantified by HPLC. Clonidine, tolazoline and agmatine concentration-dependently induced a release of histamine from the gastric strips, whereas BDF 6143 was ineffective. However, BDF 6143 abolished the release-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…However, a ganglionic mechanism can not be excluded since, (1) the presynaptic imidazoline binding site was pharmacologically characterized as belonging to a non I 1 ‐/ non I 2 ‐subclass (Molderings & Göthert, 1999); (2) I 1 ‐binding sites are present at the cell bodies of sympathetic ganglia and adrenal medulla (Molderings et al ., 1993); and (3) agmatine blocks nicotinic‐cholinergic transmission in sympathetic ganglia (Loring, 1990). Furthermore, since activation of I 1 ‐binding sites releases prostaglandins (Ernsberger et al ., 1995) and histamine (Molderings et al ., 1999), which have both been shown to diminish noradrenaline release (Wennmalm & Junstad, 1976; Göthert et al ., 1999), it also seems likely that agmatine might be able to reduce noradrenaline overflow via such an indirect mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…However, a ganglionic mechanism can not be excluded since, (1) the presynaptic imidazoline binding site was pharmacologically characterized as belonging to a non I 1 ‐/ non I 2 ‐subclass (Molderings & Göthert, 1999); (2) I 1 ‐binding sites are present at the cell bodies of sympathetic ganglia and adrenal medulla (Molderings et al ., 1993); and (3) agmatine blocks nicotinic‐cholinergic transmission in sympathetic ganglia (Loring, 1990). Furthermore, since activation of I 1 ‐binding sites releases prostaglandins (Ernsberger et al ., 1995) and histamine (Molderings et al ., 1999), which have both been shown to diminish noradrenaline release (Wennmalm & Junstad, 1976; Göthert et al ., 1999), it also seems likely that agmatine might be able to reduce noradrenaline overflow via such an indirect mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…to α 2 ‐adrenoceptors as well as to I 1 and I 2 binding sites. Some authors ( Chan, 1998 ; Molderings et al ., 1998a ; 1999a ) attributed functions to binding sites (nonl 1 /non I 2 ‐binding sites) the affinity profile of which is consistent with neither the I 1 ‐ nor the I 2 ‐binding sites.…”
Section: Imidazolin Binding Sitesmentioning
confidence: 98%
“…Furthermore, some authors have attributed specific functions such as noradrenaline release ( Fuder & Schwarz, 1993 ; Molderings & Göthert, 1995 ; Likungu et al ., 1996 ; Molderings et al ., 1999b ), secretion of gastric acid and pepsin ( Molderings et al ., 1998a ; 1999a ) and insulin from β‐cells ( Chan, 1998 ) to binding sites for which the affinity profile is not consistent with those of I 1 ‐ or I 2 ‐binding sites (nonI 1 /non I 2 ‐binding sites see Figure 1).…”
Section: Imidazolin Binding Sitesmentioning
confidence: 98%
See 1 more Smart Citation
“…In view of this, another hypothetical mechanism may involve an effect on noradrenaline release mediated via I 1 -binding sites. Because stimulation of ganglionic I 1 -binding sites releases prostaglandins (Ernsberger et al, 1995) and histamine (Molderings et al, 1999b), which were both shown to diminish noradrenaline release from the sympathetic nerves of cardiovascular and other tissues (Starke and Montel, 1973;Levi and Smith, 2000), it is likely that agmatine reduces noradrenaline overflow via such an indirect mechanism. Finally, nicotine was shown to increase catecholamine release by activating nAch receptors localized on peripheral postganglionic sympathetic nerve endings and in the adrenal medulla (Anden et al, 1986).…”
Section: Discussionmentioning
confidence: 99%